Proof technology and computation - Schwichtenberg, Helmut, 1942-; Spies, Katharina (NATO science series. Computer and systems sciences ;, 2006)
Software engineers have integrated proof processing into industrial development tools, and these implementations are now getting very efficient. The chapters deal with: The benefits and technical challenges of sharing formal mathematics among interactive theorem provers; proof normalization for various axiomatic theories; abstraction-refinement framework of temporal logic model checking; formal verification in industrial hardware design; readable machine-checked proofs and semantics and more.